PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN CILEDUG KOTA TANGERANG - Miftahudin Asshidqi; Ratna Sari (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of work discipline and work environment on employee performance at the Ciledug District Office, Tangerang City. This type of research is a quantitative research type using the associative method. The data collection technique used the questionnaire method, the population in this study were all employees of the Ciledug District Office, namely 50 employees using saturated samples. The data analysis technique in this study was statistics using validity testing, reliability testing, classical assumption testing, determination coefficient testing, hypothesis t-test and hypothesis f-test. The results of the study on the effect of work discipline and work environment on employee performance at the Ciledug District Office, Tangerang City are shown by the multiple linear regression equation Y = 1.806 + 0.471 X1 + 0.487 X2. This is evidenced by the results of the simultaneous hypothesis test obtained F count> F table or 113.587> 3.20 and reinforced by a significance value of 0.000 <0.05. The results of the coefficient determination test of the work discipline (X1) and work environment (X2) variables gave an influence of 82.9% on employee performance at the Ciledug District Office, Tangerang City. Thus, H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between work discipline (X1) and work environment (X2) on employee performance (Y).